Performance characteristics of bioassay UV-spectrophotometry and high perfomance liquid chromatographic determination of gatifloxacin in tablets - Lopes, Cristiani Capistrano Gonçalves de Oliveira [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Sociedade Brasileira de Química, 2008)
The microbiological bioassay, UV-spectrophotometry and HPLC methods for assaying gatifloxacin in tablets were compared. Validation parameters such as linearity, precision, accuracy, limit of detection and limit of quantitation were determined. Beer's law was obeyed in the ranges 4.0-14.0 μg/mL for HPLC and UV-spectrophotometric method, and 4.0-16.0 μg/mL for bioassay. All methods were reliable within acceptable limits for antibiotic pharmaceutical preparations being accurate, precise and reproducible. The bioassay and HPLC are more specific than UV-spectrophotometric analysis. The application of each method as a routine analysis should be investigated considering cost, simplicity, equipment, solvents, speed, and application to large or small workloads.
Keywords: fluoroquinolone; gatifloxacin; pharmaceutical analysis